Pengaruh Transparansi Dalam Sistem Pengendalian Intern Dan Sistem Informasi Akuntansi Terhadap Akuntabilitas Pengelolaan Dana Desa Guna Kesejahteraan Masyarakat - Windarti Widyaningrum; Dede Rusdi (Politeknik Raflesia Press, 2025)
— Village funds are financial allocations provided by the central government to village administrations to support governance, development, and community welfare. Public sector accountability requires organizations to report responsibly to both internal and external stakeholders. Therefore, village fund management must be conducted properly, transparently, and accountably. Indonesia Corruption Watch (ICW) has reported recurring cases of fund misuse, with village fund management being one of the most frequent, which highlights the urgency of accountability in village governance. This study aims to analyze the influence of accounting information systems on village fund management, the level of transparency in village administrations, and the role of internal control systems in supporting accountable management. Data were collected through questionnaires distributed directly to village officials in Demak Regency. Using a saturated sampling technique, 95 respondents were obtained, and the data were analyzed with multiple linear regression using IBM SPSS Statistics 25. The findings reveal that transparency, internal control systems, and accounting information systems have a significant influence on the accountability of village fund management. These results emphasize the importance of openness, adequate control mechanisms, and the effective use of accounting information technology to ensure accountable village fund management that ultimately supports community welfare.